KARAKTERISTIK BIOTURBASI OLEH RAMA-RAMA (Thalassina spp.) DI LINGKUNGAN PESISIR BUKIT BATU, BENGKALIS, RIAU - Rusmaniar '; Ahmad Muhammad; Windarti ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Rama-rama is one of typical macrofauna from the mangrove ecosystem. The existence of this organism can be seen easily from the appearance of mud mounds in the ground surface as a result of bioturbation activity. The purposes of this research were to understand rama-rama species in the coastal area of Bukit Batu and the characteristic of bioturbation conducted by this organism and also to obtain the valuation of important impact of this activity to its environment. This research had been conducted from September to November 2013 in Bukit Batu and Tanjung Leban villages. Observation was conducted in four line transects, 1100 m length, from the edge of the water during the lowest tide. There were 10 transects (10 m x 10 m) placed along the line (100 m interval). The diameter and height of mud mounds, diameter of the hole, soil bulk density and the ability of rama-rama in carrying the soil / day were observed. Information on impact of the presence of the rama-rama on the social condition of people was obtained by interviewing people living around the coast. The results show that there were 2 species of Thalassina, namely T. anomala and T. spinosa. Rama-rama bioturbation activities were influenced by its body size and soil bulk density. The average of soil carrying capacity of each rama-rama was 740 cm3/mound/day. Therefore, with the average density of mound was 3,9 mound/m2, the soil carried was around 2900 cm3 /m2/ day or 11.000 m3/ha. It can be concluded that the soil carrying capacity of the rama-rama is potential to affect the coastal area environment.